Plants derived therapeutic strategies targeting chronic respiratory diseases: Chemical and immunological perspective. (1st July 2020) - Prasher, Parteek; Sharma, Mousmee; Mehta, Meenu; Paudel, Keshav R.; Satija, Saurabh; Chellappan, Dinesh K.; Dureja, Harish; Gupta, Gaurav; Tambuwala, Murtaza M.; Negi, Poonam; Wich, Peter R.; Hansbro, Nicole G.; et al.
Abstract: The apparent predicament of the representative chemotherapy for managing respiratory distress calls for an obligatory deliberation for identifying the pharmaceuticals that effectively counter the contemporary intricacies associated with target disease. Multiple, complex regulatory pathways manifest chronic pulmonary disorders, which require chemotherapeutics that produce composite inhibitory effect. The cost effective natural product based molecules hold a high fervor to meet the prospects posed by current respiratory-distress therapy by sparing the tedious drug design and development archetypes, present a robust standing for the possible replacement of the fading practice of poly-pharmacology, and ensure the subversion of a potential disease relapse. This study summarizes the experimental evidences on natural products moieties and their components that illustrates therapeutic efficacy on respiratory disorders. Highlights: Plant derived therapeutics for managing chronic respiratory disorders. Activity of natural product based molecules on key regulatory pathways of COPD. Preclinical evidence for the efficacy of natural product moieties. Clinical significance of plant derived molecules in pulmonary distress.